Proliferating status of peripheral blood progenitor cells from patients with BCR/ABL-positive chronic myelogenous leukemia - Krämer, Alwin; Löffler, Harald; Bergmann, Jörg Stefan; Hochhaus, Andreas; Hehlmann, Rüdiger (Leukemia, 2001)
To investigate the mechanisms behind the leukemic expansion of BCR/ABL-positive chronic myelogenous leukemia (CML), we examined the cell cycle status of hematopoietic progenitor cells from peripheral blood (PB) and bone marrow (BM) of 37 patients with newly diagnosed BCR/ABL-positive CML. We found a high proportion of 12.51 ± 1.19% of CD34+peripheral blood progenitor cells (PBPC) in S/G2M phase. Comparison of PB and BM from 19 cases revealed similar proliferation rates (10.74 ± 1.41% vs 15.97 ± 1.95%). Furthermore, even primitive CD34+/CD38− PBPC displayed high proliferation rates (17.45 ± 2.98%) in 10 cases examined. In contrast, PBPC from 11 patients with BCR/ABL-negative myeloproliferative disorders were almost noncycling (S/G2M 1.46 ± 0.47%). When matched pairs of PB and BM from six patients with BCR/ABL-negative myeloproliferative disorders were examined, only 0.89 ± 0.41% of the CD34+ PBPC, but 8.29 ± 3.13% CD34+ cells from BM were in S/G2M phase. Consistently, as compared to 19 patients with newly diagnosed BCR/ABL-positive CML, a significantly lower PB/BM ratio of CD34+ cells in S/G2M phase was found in these six patients with BCR/ABL-negative myeloprolifrative disorders. Administration of the tyrosine kinase inhibitor STI571 to 13 patients with CML in chronic phase, accelerated phase, or blast crisis lead to an inhibition of PBPC proliferation within a few days. Interestingly, CD34+ hematopoietic progenitor cells from BM remained proliferating in five cases examined, indicating that CML PBPC are more easily inhibited by STI571 as compared to CD34+ CML hematopoietic progenitor cells from BM. These data suggest that BCR/ABL leads to an enhanced cell cycle activation of CD34+ cells, which seems to be, at least in part, independent of additional factors provided by the bone marrow microenvironment.